The Relationship between Attributional Style and Emotion Regulation Styles with Social Well-Being in Students - Akbarnia, Hadis; Vatankhah, Hamid Reza (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study investigated the relationship between attribution styles, emotion regulation styles, and social well-being among students.Methods and Materials: This study was both descriptive and correlational. The target population for this research comprised all secondary-level students in the 18th district of Tehran during the second semester of the academic year 2022-23. A sample size of 150 individuals was determined based on Krejci and Morgan's (1970) table and selected randomly (Krejcie, 1970). Questionnaires were utilized to gather data on attribution styles (Seligman et al., 1979), emotion regulation styles (Garnefsky et al., 2001), and social well-being (Keyes, 1998) in this study. The data in this study was examined utilizing SPSS version 23 software at both descriptive and inferential stages.Findings: Results indicated that attribution and emotion regulation styles accounted for 23% of the variance in social well-being (p < 0.01), with negative emotion regulation and positive attribution styles contributing significantly to this variance.Conclusion: Based on the conclusions drawn from this study, which indicate that social well-being can be forecasted by individuals' attribution events and regulate their emotions, it is recommended that schools introduce educational initiatives aimed at enhancing students' emotional regulation abilities and cultivating healthy strategies for attributing life experiences.